2001
DOI: 10.1051/0004-6361:20000344
|View full text |Cite
|
Sign up to set email alerts
|

A new analysis of the radial velocity variations of the eclipsing and spectroscopic binary EN Lacertae

Abstract: Abstract. An analysis of 1236 new electronic spectra of the eclipsing binary EN Lac from four observatories and of 994 radial velocities (RV hereafter) from photographic spectra, published by several authors, has allowed us to disentangle the RV variations due to orbital motion and due to pulsations of the star. New, accurate orbital elements as well as precise values of the three pulsation periods, already known from the previous studies, were derived. The accuracy of the orbital solution has been substantial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
3
16
0
Order By: Relevance
“…EN (16) The first spectroscopic mode identification for this star was recently done by who considered a subset of 940 high-resolution high S /N spectra gathered by Lehmann et al (2001). Our mode identification presented here, which was done using K 1 = 0.0824, K 2 = 0.0841 and K 3 = 0.0951, is one of the identification results adapted by , who considered also other spectroscopic diagnostics for identification.…”
Section: En (16) Lacertaementioning
confidence: 99%
“…EN (16) The first spectroscopic mode identification for this star was recently done by who considered a subset of 940 high-resolution high S /N spectra gathered by Lehmann et al (2001). Our mode identification presented here, which was done using K 1 = 0.0824, K 2 = 0.0841 and K 3 = 0.0951, is one of the identification results adapted by , who considered also other spectroscopic diagnostics for identification.…”
Section: En (16) Lacertaementioning
confidence: 99%
“…BW Vul is a binary system (P orb = 33.3 ± 0.3 y, Pigulski 1992) with the secondary component 6−10 mag fainter than the primary. EN Lac is an eclipsing binary with orbital period 12.0968 d (Pigulski & Jerzykiewicz 1988;Lehmann et al 2001, and references therein). The secondary component is fainter than the primary by about 5 mag.…”
Section: The Observational Materialsmentioning
confidence: 99%
“…This star has been studied by many authors. We refer to Chapellier et al (1995) and Lehmann et al (2001) for a summary of the observational studies and to Dziembowski & Jerzykiewicz (1996) for the first seismic study of this β Cephei star. In this section, we illustrate the process we term non-adiabatic asteroseismology, by deriving constraints on the metallicity of the star.…”
Section: The β Cephei Star En (16) Lacmentioning
confidence: 99%
“…In this section, we illustrate the process we term non-adiabatic asteroseismology, by deriving constraints on the metallicity of the star. The three observed frequencies used in our study were taken from Lehmann et al (2001) and the photometric amplitudes obtained with Johnson filters were derived by Jerzykiewicz (1993). Aerts et al (2002) showed convincingly that the spectroscopic mode identification is fully compatible with the photometric one for this star, and points towards a radial mode for the first frequency ( f 1 = 5.9112 c d −1 ), an = 2 mode for the second frequency ( f 2 = 5.8551 c d −1 ) and an = 1 mode for the third frequency ( f 3 = 5.5033 c d −1 ).…”
Section: The β Cephei Star En (16) Lacmentioning
confidence: 99%